Antibiotic Hypersensitivity Mechanisms - Jenana H. Maker; Cassandra M. Stroup; Vanthida Huang; Stephanie F. James (MDPI AG, 2019)
Antibiotics are commonly prescribed to treat a variety of bacterial infections. As with all medications, hypersensitivity reactions may occur and clinicians should be able to recognize them accurately and recommend appropriate management. Antibiotic related hypersensitivity reactions may be one of four different types: Type I reactions, which are IgE mediated and may lead to anaphylaxis; Type II reactions that are antibody-mediated and may result in thrombocytopenia, neutropenia, or hemolytic anemia; Type III reaction that involves an immune complex formation such as vasculitis; and Type IV reactions that consist of four subtypes and typically include a rash of varying level of severity with or without systemic signs and symptoms. Herein, we describe the mechanisms of different types of allergic reactions to commonly prescribed antibiotics and offer recommendations for management. Further, we briefly refer to antibiotic reactions that mimic hypersensitivity reactions but are not immune mediated, such as pseudoallergies and serum sickness-like reactions.